2005
DOI: 10.1001/archsurg.140.4.353
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Experience With Liver Transplantation for Hepatocellular Carcinoma

Abstract: Hypothesis: Liver transplantation (LT) has become the optimal treatment for stages I and II hepatocellular carcinoma (HCC). Based on our 20-year experience, changes in staging, techniques, and patient selection have improved survival over the past 20 years. Herein, we determine if pre-LT treatment for HCC alters the longterm outcomes in patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…recurrence [7,11,15]. To improve patients`outcome, it is of great clinical importance to find reliable prognostic markers, which could predict relapse and dissemination of HCC.…”
mentioning
confidence: 99%
“…recurrence [7,11,15]. To improve patients`outcome, it is of great clinical importance to find reliable prognostic markers, which could predict relapse and dissemination of HCC.…”
mentioning
confidence: 99%
“…The part of liver tissue obtained by needle biopsy, in many instances, particularly in cases of CLD fails to provide a correct assessment of changes in the whole liver [15,18]. Some of the recent reports on the epidemiology of different types of end-stage CLD in the general population and their future projections have been based, to a significant extent, on data from LT centers [2][3][4]. A review of the etiologic assessment of CLD (even though not done in as extensive a manner as in our LT cases) in a much larger number of cases seen in our hospital liver clinics over the same period of time showed frequencies of the different categories to be very similar to those in the study reported here.…”
Section: Discussionmentioning
confidence: 99%
“…If not detected and treated early, a number of these progress to an irreversible stage, become refractory to treatment, and invariably lead to fatal complications. Success in liver transplantation (LT) achieved during the last two decades has provided substantial relief to such cases of end-stage CLD [1][2]. Besides, analyses of data from different LT centers in developed countries have yielded a considerable important information such as epidemiology and temporal changes in end-stage CLD [1,[2][3][4], detection of precancerous lesions and small cancers in the liver [6,7] as well as selection, prioritization, and management of cases in an LT program [1,2,6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of preoperative recognition, the concomitant presence of hemochromatosis and HCC or cholangiocellular carcinoma did not influenced short-term survival (55 vs. 58%). A few other additional studies report on liver transplantation and HCC in the context of HH [21,22] . However, the lack of adequate information available on the outcome of these patients prevented us from including them in our analysis.…”
Section: Review Of the Literature With Reference To Resectability Ratmentioning
confidence: 99%